Can the renewed interest in ultra-long-range passenger flights be satisfied by the current generation of civil aircraft?. Issue 2 (3rd April 2017) - Baxter, Glenn S.; Bardell, Nicholas S.
Abstract: A number of full service network carriers have recently stated their ambition to develop certain ultra-long-range (ULR) routes, such as Doha to Auckland, Dubai to Auckland, Dubai to Panama City, Singapore to San Francisco, Singapore to New York, all of which require a great circle distance between 7, 000–9, 000 nautical miles (nm) with an estimated travel time between 15 and 20 hours. This paper examines the capability of the current generation of wide-bodied passenger aircraft to satisfy this evolving strategy, and the impact, if any, on the provision of air cargo transportation. An exploratory study is presented herein based on an assessment of each aircraft type's payload-range envelope, taken from the appropriate Aircraft Airports Handling Characteristics Manual. The key findings reveal that airlines wishing to pursue this ultra-long-range strategy have a surprisingly limited choice of current-generation passenger aircraft which are capable of flying the desired mission profile without compromising significantly on passenger numbers and cargo payload.